Design of Decision Support System for Selection of Outstanding Students Using AHP and Promethee Methods - Dachi, Surya Wisada (Al'Adzkiya, 2022)
Student affairs often has difficulty in determining students that are sent to events because of many outstanding students at the institution. So far, the sending of students is still intuitive and subjective. Therefore, this research aims to design and build a decision support system that can provide advice to determine the best student that will be sent to the event. In this research, the method of decision support system that is used is a combination of AHP and Promethee. In implementation, AHP is executed to get criteria weight. After that, Promethee is executed to determine the order of candidates priority. The purpose of combination is to increase the quality of advice about the selection of students. The result of research shows that with the decision support system that is built, student affairs can choose the students that are sent to events more quickly, accurately, and objectively. Gist-The student affairs department often has difficulty in determining outstanding students who will be sent to events due to the large number of outstanding students in the institution. Due to the absence of a decision support system, sending students so far is still intuitive and subjective. Therefore, this research aims to design and build a decision support system that can provide advice to determine the best students to be sent to the event. In this case, the decision support system method used is a combination of Analytical Hierarchy Process (AHP) and Promethee. In its application, AHP is run first to get the weight of the criteria. After that, Promethee is run to determine the priority order of prospective event participants. The purpose of this combination is to improve the quality of student selection advice. The results showed that with this decision support system, the student affairs department can select students who are sent to an event more quickly, precisely, and objectively.